One Legacy of Paul F. Brandwein Creating Scientists - Fort, Deborah C. (Classics in Science Education,, 2010)
This book includes a brief biography of Paul Brandwein, but its most vital contribution are the essays about Paul F. Brandweins teaching that encouraged a number of the high school students he taught between 1944 and 1954 at Forest Hills High School in New York to become some of Americas most important scientists. In addition to the individual essays, there are cross-sectional study of the surveys returned by the 29 "Brandwein alumni," located by Richard Lewontin, James Friend, the late Walter Rosen, and Deborah Fort over the years since Paul Brandweins death in 1994. Creating Scientists might point the way to a replicable method that teachers (often, in addition, serving as mentors) could follow in encouraging their precollege students with a bent for science to choose to follow that inclination into postsecondary studies and eventually careers in science, mathematics, engineering, medical, and technical fields. "Once again, our nation has a powerful need for a revolution devoted to creating scientists. As we face the challenges of climate change, global competitiveness, biodiversity loss, energy needs, and dwindling food supplies, we find ourselves in a period where both scientific literacy and the pool of next-generation scientists are dwindling. To solve these complex issues and maintain our own national security, we have to rebuild a national ethos based on sound science education for all, from which a new generation of scientists will emerge. The challenge is how to create this transformation. Those shaping national policy today, in 2009, need look no further than what worked a half-century ago. ... Paul F. Brandwein spent his professional life as a scientist, educator, author, and publisher focused on the deep question of how we as a nation can create the scientist within. Through varied contributions from his former students, his colleagues, and his friends, One Legacy of Paul F. Brandwein: Creating Scientists explores how one mans teachings and philosophies on science, education, and environmentalism both laid the groundwork for the first great science education revolution in our nations history and prepared the way for the one so necessary today. Many of the essays in this book offer firsthand reflections by former students and colleagues of Pauls during the 1950s and beyond that record the impact of, and inspiration that resulted from, their encounters. Pauls insights highlighted in this book illuminate a path forward for us today, as we work to create the second American science education revolution." Keith A. Wheeler, President, The Paul F-Brandwein Institute, Unionville, New York, USA